TO THE QUESTION ABOUT THE USE OF DC TRACTION MOTORS SYSTEM OF THE ELECTRIC ROLLING STOCK OF THE RAILWAYS - Dubynets, L. V.; Marenych, O. L.; Mukha, A. M. (Science and Transport Progress, 2008)
Issues of expediency of using the DC traction engines on multi-system electric railway rolling stock are considered in the paper.